Motor traffic on urban minor and major roads: impacts on pedestrian and cyclist injuries. Issue 1 (16th May 2018) - Aldred, Rachel
Abstract : This paper compares per-mile risks posed by motor traffic to pedestrians and cyclists on urban major and minor roads. Carrying out new analysis of police injury data from 2005 to 2015, this study finds that per billion vehicle miles, motor vehicles on minor roads create more pedestrian casualties than motor vehicles on major roads. Specifically, for killed or seriously injured (KSI) casualties the rate per billion motor vehicle miles is 17% higher on minor roads (47 against 40 KSIs per billion vehicle miles), while for slight injuries it is 66% higher (188 against 123 slight injuries per billion vehicle miles). Examining the costs of injuries sustained, these are 7·4% higher for pedestrians per motor vehicle mile travelled on urban minor roads, compared with major roads. For cyclists, injuries per mile driven are similar on major and minor roads. These results suggest that re-routing motor traffic to major roads in urban areas may reduce pedestrian casualties. Cyclist safety on major roads should be improved to avoid unintended negative consequences and ensure positive outcomes for cycling.